2009
DOI: 10.1088/1674-1056/18/1/011
|View full text |Cite
|
Sign up to set email alerts
|

Hawking radiation from the dilaton—(anti) de Sitter black hole via covariant anomaly

Abstract: Adopting the anomaly cancellation method, initiated by Robinson and Wilczek recently, this paper discusses Hawking radiation from the dilaton—(anti) de Sitter black hole. To save the underlying gauge and general covariance, it introduces covariant fluxes of gauge and energy-momentum tensor to cancel the gauge and gravitational anomalies. The result shows that the introduced compensating fluxes are equivalent to those of a 2-dimensional blackbody radiation at Hawking temperature with appropriate chemical potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…In the past few decades, the thermodynamic properties of black holes have attracted increasing interest, and a considerable amount of work related to the thermal radiation of black holes has been done. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Starobinsky and Unruh have demonstrated that for a rotating black hole or a charged black hole, not only is there thermal radiation, but also nonthermal radiation. [18,19] In recent years, the study of the nonthermal radiation of black holes has also achieved a great deal of progress.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, the thermodynamic properties of black holes have attracted increasing interest, and a considerable amount of work related to the thermal radiation of black holes has been done. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Starobinsky and Unruh have demonstrated that for a rotating black hole or a charged black hole, not only is there thermal radiation, but also nonthermal radiation. [18,19] In recent years, the study of the nonthermal radiation of black holes has also achieved a great deal of progress.…”
Section: Introductionmentioning
confidence: 99%